An Action Research Study on the Development of Object-Oriented Programming Course - ÖZDENER DÖNMEZ, NESRİN (My University, 2021)
Computer games are effective instructional tools used in programming courses to increase students' motivation and engagement. This participatory action research aims to redesign the Object-Oriented Programming course in which the first author is both the instructor and researcher to make it more effective and efficient. In the first step of the action research, data were collected for the definition and solution of the problem through questionnaires and semistructured interviews. After this step, an action plan was created, and the ObjectOriented Programming course was redesigned as part of the action plan. In line with the objectives of the action plan, The Karting Microgame Template, a game prototype prepared by Unity 3D, was integrated into the course, and students were expected to add various game components (bonus collection system, a scoring system, collision mechanisms, etc.) to this game prototype using C # programming language. After the action plan creation phase, an action plan was implemented. The implementation phase was conducted in the 2019-2020 spring semester with 29 post-secondary students enrolling in Computer Technology Department at a vocational college in Turkey. After the implementation phase, data were collected through the Object-Oriented Programming achievement test, student and researcher diaries, and focus group interviews on measuring this implementation's effectiveness. This paper describes the difficulties encountered during the study, the students' views on this implementation, and the researchers' experiences in this process.
Keywords: Action research; Game programming; Programming education; Object-oriented programming course